Investigating the manifestations of thought in Qeysar Aminpour's poetry - سیّده مریم ابوالقاسمی; شهلا علیه پور (تاریخ ادبیات)
Diversity in subject and content is one of the main features of Qeysar Aminpour's poetry. In his poetry, he has paid special attention to various topics such as social issues, contrast between tradition and innovation, conflict between human beliefs and imaginations and existing realities, freedom, idealism, expectation, etc. In Qeysar's poems, social issues are prominent and especially important, and most of his poetic themes serve society and its related issues. Qaiser's early poetry collections have a scholastic-professional theme and are mixed with epic and mysticism and are full of idealism and anti-tyranny, which gradually turns into a human-oriented, realistic, individualistic and world-oriented poetry. In this way, in the next collections of his poetry, he begins a movement from rhetorical poetry to intelligent and cultured poetry. In this article, the various manifestations of thought and thinking in Qeysar Aminpour's poetry have been examined and pondered in order to determine the aspects of his mental and intellectual index.